Ecological Competence Formation of Future Agricultural - Romaskevych, Alina; Sytnychenko, Viktor; Olchedaievskyi, Yuriy (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The problem of ecologization of agricultural education is discussed in the article. The technology of ecological competence formation of future agricultural specialists is offered.
Keywords: educational paradigm; ecologization of education; ecological competence; technology; pedagogical technology; agricultural specialists